ХЭРЭГЛЭГЧДИЙН СЭТГЭЛ ХАНАМЖ НЬ БРЭНДЭД ҮНЭНЧ БАЙДАЛД НӨЛӨӨЛӨХ НЬ - Ч.Батбаатар; Ц.Цолмон (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Purpose of this study is to determine whether customer satisfaction causes direct impact on brand loyalty and brand reputation can be more influential than other factors for purchase decision of mobile phones. Any business organization aims to keep its customer satisfaction high and tries to build strong base of loyal customers. To define these relationships in more detailed, sophisticated way the study tries to identify how the customer satisfaction connects to brand loyalty and factors influencing buying decision among mobile phone users in Ulaanbaatar. The study revealed following results after using primary and secondary research methods. (1) Market share and brand loyalty of big brands like Apple and Samsung are continuously declining as a result of tight competition in mobile phone market. As the product life cycle shortens brands tend to increase number of models they are offering to the market. (2) In Mongolia, brands such as Apple and Samsung own a big share of the market (more than 50 percent combined), however, customer satisfaction and brand loyalty have been higher in case of iPhone than Samsung phones users. (3) The study assured that there is a direct relationship between customer satisfaction and brand loyalty. Moreover, the results suggest that brand reputation can be less important to purchase decisions than the main factors such as battery, camera, storage, capacity, network coverage, design, price and reliability of dealers.